2014
DOI: 10.1007/s00246-014-0939-x
|View full text |Cite
|
Sign up to set email alerts
|

Admission to a Dedicated Cardiac Intensive Care Unit Is Associated With Decreased Resource Use for Infants With Prenatally Diagnosed Congenital Heart Disease

Abstract: Many factors in the delivery and perinatal care of infants with a prenatal diagnosis of congenital heart disease (CHD) have an impact on outcome and costs. This study sought to determine the modifiable factors in perinatal management that have an impact on postnatal resource use for infants with CHD. The medical records of infants with prenatally diagnosed CHD (August 2006-December 2011) who underwent cardiac surgery before discharge were reviewed. The exclusion criteria ruled out prematurity and intervention … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 24 publications
1
10
0
Order By: Relevance
“…Johnson and colleagues 5 found that 39% of neonates were admitted to the CICU, 48% to the NICU, and 13% to the PICU. Consistent with the findings of their previous work, 4 they found that admission to the CICU was associated with a significant cost reduction when compared with admission to the NICU. Further, admission to the CICU was associated with a shorter LOS and fewer days of mechanical ventilation.…”
supporting
confidence: 89%
See 2 more Smart Citations
“…Johnson and colleagues 5 found that 39% of neonates were admitted to the CICU, 48% to the NICU, and 13% to the PICU. Consistent with the findings of their previous work, 4 they found that admission to the CICU was associated with a significant cost reduction when compared with admission to the NICU. Further, admission to the CICU was associated with a shorter LOS and fewer days of mechanical ventilation.…”
supporting
confidence: 89%
“…2,3 Further, admission to a dedicated cardiac intensive care unit (CICU) was found to be associated with decreased resource use in a single-institution study. 4 Johnson and colleagues, 5 the same group that conducted that earlier study, 4 report in this edition of the Journal a confirmation of their initial findings with a multicenter study of data from the Pediatric Hospital Information Systems (PHIS) database.…”
mentioning
confidence: 65%
See 1 more Smart Citation
“…9,26,27 The advantages of in utero transportation vs postnatal transportation of infants with CHD, including maternal and neonatal safety and costs, vary according to the obstetric and pediatric resources of a specific region. 31 Finally, a prospective multicenter study showed that postnatal diagnosis of CHD was associated with higher costs, compared to those with prenatal diagnosis, due to the need for emergency transportation. 24,28,29 Recent studies have investigated the costs of specialized delivery and early postnatal management in pregnancies complicated by fetal CHD.…”
Section: Delivery Planning Of Fetuses With Chd: Multidisciplinary Amentioning
confidence: 99%
“…In another retrospective study, prenatally diagnosed infants with CHD admitted to the cardiac intensive care unit (ICU) compared to those admitted to the neonatal ICU had shorter length of stay, less mechanical ventilation, and lower costs of care. 31 Finally, a prospective multicenter study showed that postnatal diagnosis of CHD was associated with higher costs, compared to those with prenatal diagnosis, due to the need for emergency transportation. 32 While these results suggest that prenatal diagnosis of CHD and management in the proper ICU setting can potentially reduce healthcare costs for these conditions, further studies investigating this topic are needed.…”
Section: Delivery Planning Of Fetuses With Chd: Multidisciplinary Amentioning
confidence: 99%